Assessment of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and mean platelet volume in patients with tinnitus - Alper Bayram, Ali; Yaşar, Mehmet; Doğan, Murat; Güneri, Erhan; Özcan, İbrahim (ENT Updates, 2015)
Objective: The aim of this retrospective, case-control study was to investigate the association of neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and mean platelet volume (MPV) with tinnitus. Methods: A total of 51 patients with tinnitus and 42 healthy, age- and sex-matched subjects were recruited for the present study. Audiometric data including pure-tone average (PTA) values, the side of the head in which tinnitus was experienced, duration of tinnitus, tinnitus reaction questionnaire (TRQ), tinnitus handicap questionnaire (THQ), complete blood count (CBC) and biochemical data were assessed from patient records. The mean values of NLR, PLR and MPV were compared between patients with tinnitus and healthy controls. Results: The difference was not significant for mean serum NLR, PLR and MPV values between patients with tinnitus and healthy controls. Conclusion: Serum NLR, PLR and MPV levels may not be useful parameters for routine clinical evaluation of tinnitus.